Congenital Anomalies of the Kidney and the Urinary Tract (CAKUT). Issue 2 (April 2016) - Liut, Francesca; Izzi, Claudia; Dallera, Nadia; Scolari, Francesco
Congenital Anomalies of the Kidneys and the Urinary Tract (CAKUT) involves several morphological anormalies of the kidneys and the urinary tract directly linked to congenital defects of kidney embryogenesis. It represents about 23% of all congenital defects, 50% of End-Stage Renal Disease (ESRD) in pediatric patients and 2–7% of ESRD in adult patients. CAKUT includes a wide spectrum of morphological anomalies of the kidneys and the urinary tract with heterogeneous case histories and modalities of transmission from severe to familiar ones, sporadic, autosomal recessive or closely linked to de novo mutations. Environmental factors can also be involved as clearly highlighted by the association between pregnancy-related diabetes mellitus and renal agenesia and/or alcohol or cocaine abuse. CAKUT pathogenesis is multifactorial but renin-angiotensin system encoding gene mutations seems to be involved in CAKUT development. Only 10% of all CAKUT patients present diagnosed genetic mutations at present time. Due to the wide spectrum of disease's onset and the different impact of renal anomalies, a clinical approach tailored to every single patient with an extended follow-up period and an accurate genetic counseling is mandatory.